2017
DOI: 10.1038/srep43584
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Mediator Complex Interactome in Saccharomyces cerevisiae

Abstract: Here we present the most comprehensive analysis of the yeast Mediator complex interactome to date. Particularly gentle cell lysis and co-immunopurification conditions allowed us to preserve even transient protein-protein interactions and to comprehensively probe the molecular environment of the Mediator complex in the cell. Metabolic 15N-labeling thereby enabled stringent discrimination between bona fide interaction partners and nonspecifically captured proteins. Our data indicates a functional role for Mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
5
14
0
Order By: Relevance
“…This notion is in agreement with both older and more recent studies in yeast (43,71,80,81), murine (82), and human cells (83) which indicate concurrent interactions of Mediator, TFIIB, and RNAPII. MS data from S.cerevisiae and from human cells identify RNAPII, TFIIB, and TFIIF among the strongest interactors of Mediator (71,83), and these factors are necessary for reinitiation (25). Notably, another recent study revealed that human genes which require de novo RNAPII recruitment for induction of transcription depend on TFIIB availability (84).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This notion is in agreement with both older and more recent studies in yeast (43,71,80,81), murine (82), and human cells (83) which indicate concurrent interactions of Mediator, TFIIB, and RNAPII. MS data from S.cerevisiae and from human cells identify RNAPII, TFIIB, and TFIIF among the strongest interactors of Mediator (71,83), and these factors are necessary for reinitiation (25). Notably, another recent study revealed that human genes which require de novo RNAPII recruitment for induction of transcription depend on TFIIB availability (84).…”
Section: Discussionsupporting
confidence: 92%
“…Mediator supports TFIIB binding to promoters, and both Mediator and TFIIB facilitate recruitment of RNAPII to promoter-bound GTFs (30). This notion is in agreement with both older and more recent studies in yeast (43,71,80,81), murine (82), and human cells (83) which indicate concurrent interactions of Mediator, TFIIB, and RNAPII. MS data from S.cerevisiae and from human cells identify RNAPII, TFIIB, and TFIIF among the strongest interactors of Mediator (71,83), and these factors are necessary for reinitiation (25).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One possible mechanism for recruitment of Mediator to sn/snoRNAs is via the interaction of activators, including Tbf1, with other subunits of Mediator, such as the tail/middle module connector Med16, which interacts with activators such as Gcn4 in yeast (49), DIF in Drosophila (53), and NRF2 in mouse and human (54). Indeed, a recent proteomic analysis of Mediator interactions reported a modest interaction between Mediator and Tbf1 (55). Mediator could also be recruited to sn/snoRNA genes independently of activators via interactions with the PIC (34,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for recruitment of Mediator to sn/snoRNAs is via the interaction of activators, including Tbf1, with other subunits of Mediator such as the tail/middle module connector Med16, which interacts with activators such as Gcn4 in yeast (45), DIF in Drosophila (50), and NRF2 in mouse and human (51). Indeed, a recent proteomic analysis of Mediator interactions reported a modest interaction between Mediator and Tbf1 (52). Mediator could also be recruited to sn/snoRNA genes independent of activators via interactions with the PIC (33, 53) (bioRxiv: https://doi.org/10.1101/207282).…”
Section: Discussionmentioning
confidence: 99%